2016
DOI: 10.1016/j.afos.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in East Asia: Current issues in assessment and management

Abstract: The greatest burden of hip fractures around the world is expected to occur in East Asia, especially China. However, there is a relative paucity of information on the epidemiology and burden of fractures in East Asia. Osteoporosis is greatly under-diagnosed and under-treated, even among the highest-risk subjects who have already suffered fractures. The accessibility to bone densitometry, the awareness of the disease by professionals and the public, and the use and reimbursement of drugs are some of the areas wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 150 publications
(214 reference statements)
0
46
0
1
Order By: Relevance
“…It has been estimated that one in three women and one in five men aged over 50 years will experience osteoporotic fractures worldwide, making the identification of risk factors of fracture an important public health issue. Such issue is particularly of concern in East Asia as the population aged over 60 years has an exponential increase in recent years, leading to a projection of high annual incidence of fractures in near future . The use of various classes of medication has been identified as a risk factor for fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that one in three women and one in five men aged over 50 years will experience osteoporotic fractures worldwide, making the identification of risk factors of fracture an important public health issue. Such issue is particularly of concern in East Asia as the population aged over 60 years has an exponential increase in recent years, leading to a projection of high annual incidence of fractures in near future . The use of various classes of medication has been identified as a risk factor for fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Such issue is particularly of concern in East Asia as the population aged over 60 years has an exponential increase in recent years, leading to a projection of high annual incidence of fractures in near future. 3 The use of various classes of medication has been identified as a risk factor for fracture. Using large databases, a number of pharmacoepidemiology studies showed that medications, such as antidiabetic 4 and antihypertensive 5 drugs, are associated with fracture risk, demonstrating the importance of utilizing databases in pharmacoepidemiology study of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Oral bisphosphonates, particularly alendronate, are the most commonly prescribed anti-osteoporosis medication in the region [14][15][16]; however, two out of three patients in Asia are non-adherent to oral bisphosphonates within 3-12 months of prescription [17][18][19]. As a result of the high burden and proportion of patients with imminent risk of fracture in the region, there is a strong need for more potent medications that can impact outcomes early in the course of the disease [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The USA experienced two million osteoporotic fractures in 2005 and this figure is projected to reach three million in 2025 [4,5]. Elderly population in Asia is rapidly expanding and in 2050, 50% of total hip fractures would be seen in the Asian region [6][7][8].…”
Section: Introductionmentioning
confidence: 99%